Analysis Directive Speech Act And Communication Approach Between Teachers And Students In The Learning Process - Hermansyah, Sam; Mukhlis, Mukhlis; Saleh, Oce tanah; Ramlah, Ramlah; Indrawati, Indrawati (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
The objectives of the research are to describe the types of directive speech acts of the teacher and student in learning and explain a pragmatic meaning of directive speech acts in the interaction of teacher and student in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng year of 2020/2021. This research method was a qualitative descriptive method with the purpose of getting an objective description of the teacher and student speech in the interaction of teaching and learning in class XI MIPA 2 Pondok Pesantren Al-Urwatul Wutsqaa Benteng. Data collection techniques usedin this study were uninvolved conversation techniques, recording techniques,and note-taking techniques.The data collection technique was used by researcher togain complete data regarding the types of directive speech acts.The researcher carried out the analysis includes four phases:identification,classification,interpretation, and report. Data gained in this study amounted to 16 speeches. There were 4types ofdirective speech acts from 16 speeches: types of directive speech acts questions,command,request,and prohibition.Thepragmaticmeaning found as follows: sense ofreminding, directing, commanding,pleading, recommending,and criticizing.